Words of wisdom : a Curator's Vade Mecum on Contemporary Art - Kuoni, Carin; Ammann, Jean-Christophe; Basualdo, Carlos; Block, René; Bonami, Francesco; Bos, Saskia; Breitwieser, Sabine; Cameron, Dan; Cooke, Lynne; Curiger, Bice; De Baere, Bart; De Salvo, Donna; et al. (New York : ICI (Independent Curators International) New York, 2001)
A modern update of medieval trade manuals, the go along with me (vade mecum) of itinerant craftsmen Words of wisdom : a curator's Vade Mecum on Contemporary Art is an invaluable guide book for anyone interested in contemporary art and the practice of curating. Advice to a new generation of curators from established curators of contemporary art exhibitions who over the past twenty five years have played a crucial role in shaping what we see today, and how we see it.
This book is published on the occasion of the 25th anniversary of Independent Curators International New York
Biog. auteurs [1 p.]
boek